Introduction to Counting Symbols in Early Childhood with Stick Math (STIKMA) Educational Tool Games - Simatupang, Nurhenti Dorlina; Sholichah, Sefy Amaliatus; Simanjuntak, Irena Agatha (JURNAL PENDIDIKAN USIA DINI, 2023)
This research aims to improve the ability to recognize the number symbols 1-10 using the Stick Math educational game tool (ETG STIKMA). This research method uses a quasi-experimental design with a control group to test the effectiveness of using ETG STIKMA on the ability to recognize numbers. ETG STIKMA learning media has been tested by material experts and media experts who are experienced and competent in their fields. Data collection techniques use questionnaires and observation. The material expert's validation results were 80%, then the media expert gave a result of 97%, which means that the media and materials contained in STIKMA media are suitable for use to improve the cognitive abilities of children aged 5-6 years at Fatimah Az-Zahro Kindergarten. The effectiveness test results show that children's cognitive abilities in recognizing numbers 1-10 have increased by 10.50% with a positive rating of 210.00. So, this game is appropriate and efficient for improving cognitive abilities regarding the number symbols 1-10. Keywords: educational tool games (STIKMA), counting symbol, early childhood References: Aziza, A., Pratiwi, H., & Ageng Pramesty Koernarso, D. (2020). Pengaruh Metode Montessori dalam Meningkatkan Pemahaman Konsep Matematika Anak Usia Dini di Banjarmasin. Al-Athfal : Jurnal Pendidikan Anak, 6(1), 15–26. https://doi.org/10.14421/al-athfal.2020.61-02 Diningrat, S. W. M., Janah, L., & Mardiyah, S. (2019). Modified Bottle Cap for Improving Children’s Arithmetic Ability. JPUD - Jurnal Pendidikan Usia Dini, 13(2), 249–263. https://doi.org/10.21009/jpud.132.04 Fathonah, R. N., & Syafdaningsih. (2021). Video Kegiatan Rote Counting dan Rational Counting untuk Menstimulasi Berhitung Permulaan pada Anak Usia (4-5) Tahun. Tumbuh Kembang : Kajian Teori Dan Pembelajaran PAUD, 8(2), 163–174. https://doi.org/10.36706/jtk.v8i2.14630 Guslinda, K. R. (2018). Media Pembelajaran Anak Usia Dini. Jakad Publiser. Hasanah, U. (2019). Penggunaan Alat Permainan Edukatif (APE) Pada Taman Kanak-Kanak Se-Kota Metro Lampung. AWLADY : Jurnal Pendidikan Anak, 5(1), 20–40. https://doi.org/10.24235/awlady.v5i1.3831 Hayati, Z. (2019). Penggunaan Alat Permainan Edukatif (APE) Dari Botol Plastik Dan Koran Bekas Untuk Meningkatkan Kreatifitas AUD. AWLADY : Jurnal Pendidikan Anak, 5(1), 56–79. https://doi.org/10.24235/awlady.v5i1.3457 Herwegen, J. Van, Costa, H. M., Nicholson, B., & Donlan, C. (2018). Improving Number Abilities In Low Achieving Preschoolers: Symbolic Versus Non-Symbolic Training Programs. Research in Developmental Disabilities, 77, 1–11. https://www.sciencedirect.com/science/article/abs/pii/S0891422218300647?via%3Dihub Indrawati, R., Darmawani, E., & Padilah. (2021). Penerapan Metode Pemberian Tugas terhadap Kemampuan Mengenal Bilangan pada Anak Usia Dini. PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 4(2), 45–52. https://doi.org/10.31849/paud-lectura.v5i02.8736 Kesicioğlu, O. S. (2021). Investigation of Counting Skills of Pre-School Children. International Journal of Progressive Education, 17(4), 262–281. https://doi.org/10.29329/ijpe.2021.366.16 Lee, J., & Md-Yunus, S. (2015). Investigating Children’s Abilities to Count and Make Quantitative Comparisons. Early Childhood Education Journal, 44(3), 255–262. https://doi.org/10.1007/s10643-015-0707-4 Lu, Y., Li, Q., Patrick, H., & Mantzicopoulos, P. (2021). "Math Gives Me a Tummy Ache!” Mathematics Anxiety in Kindergarten. Journal of Experimental Education, 89(2), 362–378. https://www.tandfonline.com/doi/full/10.1080/00220973.2019.1680518 Lumbin, N. F., Puspa Ardini, P., & Suryana Jamin, N. (2023). The Effect of Digital Card Media Towards Children’s Ability to Recognize Letters. JPUD - Jurnal Pendidikan Usia Dini, 17(1), 44–54. https://doi.org/10.21009/jpud.171.04 Rahayuningsih, S. S., Soesilo, T. D., & Kurniawan, M. (2019). Peningkatan Kemampuan Mengenal Huruf Pada Anak Usia 5-6 Tahun Melalui Metode Bermain Dengan Media Kotak Pintar. Scholaria: Jurnal Pendidikan Dan Kebudayaan, 9(1), 11–18. https://doi.org/10.24246/j.js.2019.v9.i1.p11-18 Rahma, T. D., & Widyasari, C. (2023). Analisis Kemampuan Mengenal Lambang Bilangan Anak Usia 4-5 Tahun melalui Media Kantong Buah Pintar. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 7(2), 2293–2300. https://doi.org/10.31004/obsesi.v7i2.4120 Reuben, A., Arseneault, L., Belsky, D. W., Caspi, A., Fisher, H. L., Houts, R. M., Moffitt, T. E., & Odgers, C. (2019). Residential neighborhood greenery and children’s cognitive development. Social Science & Medicine, 230, 271–279. https://doi.org/10.1016/j.socscimed.2019.04.029 Rosalianisa, R., Purwoko, B., Nurchayati, N., & Subrata, H. (2023). Analisis Kemampuan Berbahasa dan Mengenal Konsep Bilangan Anak melalui Teknologi pada Era Digital. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 7(2), 1996–2010. https://doi.org/10.31004/obsesi.v7i2.3843 Royani, I., & Suryana, D. (2023). Peningkatan Kemampuan Konsep Bilangan melaui Bermain Ular Tangga pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 7(1), 17–26. https://doi.org/10.31004/obsesi.v7i1.3480 Sarnecka, B. W., & Lee, M. D. (2019). Levels of Number Knowledge During Early Childhood. Journal of Experimental Child Psychology, 10(3), 325–337. https://www.sciencedirect.com/science/article/abs/pii/S0022096509000502?via%3Dihub Shah, P. E., Weeks, H. M., Richards, B., & Kaciroti, N. (2018). Early Childhood Curiosity and Kindergarten Reading and Math Academic Achievement. Pediatric Research, 84(3), 380–386. https://doi.org/10.1038/s41390-018-0039-3 Simon, L., Nusinovici, S., Flamant, C., Cariou, B., Valérie, R., Gascoin, G., Darmaun, D., Jean-Christophe, R., & Hanf, M. (2017). Post-Term growth and cognitive development at 5 years of age in preterm children: Evidence from a prospective population-based cohort. PLoS ONE, 12(3), 1–14. https://doi.org/10.1371/journal.pone.0174645 Svalina, V., & Vukelić, J. (2020). Connecting Mathematics and Music in Preschool Educationle. Svalina, Vesna Vukelić, Josipa, 161(3–4), 411–430. https://hrcak.srce.hr/clanak/363284 Syofriend, Y., Mafardi, Novella, T., Anggraini, V., & Priyanto, A. (2023). Stimulating Children’s Numerical Literacy: The Effectiveness of Singing Favorite Food Songs. JPUD - Jurnal Pendidikan Usia Dini, 17(1), 144–154. https://doi.org/10.21009/jpud.171.11 Umaternate, W., Haryati, H., & Mahmud, N. (2020). Penerapan Media Gelas Angka Dalam Pengembangan Kemampuan Kognitif Anak Mengenal Lambang Bilangan 1-10. Jurnal Ilmiah Cahaya Paud, 2(1), 16–29. https://doi.org/10.33387/cp.v2i1.1954 Utoyo, S., & Arifin, I. N. (2017). Model Permainan Kinestetik Untuk Meningkatkan Kemampuan Matematika Awal Pada Anak Usia Dini. JPUD - Jurnal Pendidikan Usia Dini, 11(2), 323–332. https://doi.org/10.21009/jpud.112.10 Wardani, E. K., & Suryana, D. (2022). Permainan Edukatif Setatak Angka dalam Menstimulasi Kemampuan Berfikir Simbolik Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1790–1798. https://doi.org/10.31004/obsesi.v6i3.1857 Warmansyah, J., Nola Sari, R., Febriyani, E., Mardiah, A., Marfiyenti, A., & Mahmud Yunus Batusangkar, U. (2022). The Effect of Geoquarium Magic Educational Game Tool on The Ability to Recognize Geometry Shapes in Children 4-5 Years Old. The 6 Th Annual Conference on Islamic Early Childhood Education, 6(2017), 93–100. https://vicon.uin-suka.ac.id/index.php/aciece/article/view/911#:~:text=The results got from the,Thus%2C teachers can use these Warmansyah, J., Yuningsih, R., Selva Nirwana, E., Ravidah, Putri, R., Amalina, & Masril. (2023). The Effect of Mathematics Learning Approaches and Self-Regulation to Recognize the Concept of Early Numbers Ability. JPUD - Jurnal Pendidikan Usia Dini, 17(1), 54–81. https://doi.org/10.21009/jpud.171.05 Widayati, J. R., Safrina, R., & Supriyati, Y. (2021). Analisis Pengembangan Literasi Sains Anak Usia Dini melalui Alat Permainan Edukatif. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 654. https://doi.org/10.31004/obsesi.v5i1.692 Yilmaz, Z. (2017). Young Children’s Number Sense Development: Age Related Complexity Across Cases of Three Children. International Electronic Journal of Elementary Education, 9(4), 891–902. https://www.iejee.com/index.php/IEJEE/article/view/291 Zahara, P., Valencia, A., Miftah, H., Nurainid, Nurhasanah, A., Saridewi, & Anggraini, V. (2023). Developing Aplication-based Puzzle Learning Media on Increasing Child’s Ability to Recognize Letters. International Journal of Ethnoscience, Bio-Informatic, Innovation, Invention and Techno-Science, 2(01), 44–49. https://doi.org/10.54482/ijebiiits.v2i01.192